FAKTOR-FAKTOR PENYEBAB PEMBENGKAKAN BIAYA OLEH KONTRAKTOR PROYEK JALAN KOTA SOLO - Muhammad Nur Sahid; Ika Setiyaningsih; Mochamad Solikhin; Bariq Al Salam (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
Nowadays there are some problems caused from the cost overruns that impact to losses in the implementation of road construction project. The cost overruns is very depends on several factors, both internal and external factors of the project. Thus, a high level of expertise, knowledge, and experience is needed to estimate costs from project costs to cash flow management during the implementation phase. This is done so that, in the future there will be no cost overrun that can disserve the contractors. The data that obtained from questionnaires are grouped and arranged based on thing that will be examined, to simplify and accelerate the research process. Furthermore, the data that has been grouped is processed using the SPSS program to test its feasibility as seen from the validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression test. The results of the analysis show that the dominant factors of cost overruns on road construction projects in Solo for the fiscal year 2017-2018 is the implementation time factor (X8).